Development of teenagers’ facilities of the Ukrainian hand-to-hand fight «Spas» - Лукоянова, К. В.; Панчишна, О. К.; Харченко, В. І. (Slobozhanskyi Herald of Science and Sport, 2011)
In work possibility of exercises of Ukrainian hand-to-hand fighting «Spas» as facilities of physical, functional and morally volitional development of teenagers of middle school ages. Interest of students of general schools to the national kind’s hand-to-hand fight high enough. Thus to one of main reasons which hinder wrestling, there is absence of sections. Except for it important reasons is insufficiency of spare time and rejection in a state of health.